The Loch Ness Lock-In - Cody, Matthew (Strange Scout tales, 2018)
During the annual Strange Scouts Loch Ness Lock-In, Ben and the other Strange Scouts of Troop D try to foil a dastardly plot to frame the famous monster for destroying a wind farm.